Defect formation and modulation during patterning supported graphene sheets using focused ion beams. (December 2018) - Wu, Cheng-Lun; Lin, Hsiang-Ting; Chen, Hsuan-An; Lin, Shih-Yen; Shih, Min-Hsiung; Pao, Chun-Wei
Graphical abstract: Abstract: Focused ion beams (FIB) have been employed to applications from physical to life sciences because of their capabilities of machining features with nanoscale precision, making them a promising candidate for patterning graphene. Nevertheless, there are limited applications of patterning graphene using FIB due to ion-induced damages. In this work, we performed molecular dynamics simulations and Raman spectra mapping experiments to study defect formation in Cu-supported graphene sheets during gallium ion FIB processes. Our simulation results indicate that ion bombardment induced constrained scattering of carbon atoms and sputtered copper atoms, creating more defects in graphene than patterning on free-standing graphene. We propose two approaches to mitigate FIB-induced damages: (1) lowering ion beam energy; and (2) tilting ion beam incidence angles. The first approach can effectively suppress damages with ion energy down to 1 keV; however, this is not feasible for experiments. In the second approach, we demonstrated that tilting ion incident angles result in asymmetric damage distribution, which can be leveraged to pattern graphene/2D materials by utilizing the lightly-damaged side for device fabrication while discarding the heavily damaged side. The present study reveals the formation of FIB-induced damage on supported graphene, and proposes an approach to pattern graphene/2D materials using FIB.